An Analysis of Islamic Education Evaluation Results in Madrasahs: Techniques, Interpretation, and Implementation for Continuous Improvement - Andi Irlina; Nuril Huda; Dina Hermina; Khairunnisa Khairunnisa (Tarbiyah : Jurnal Ilmiah Kependidikan, 2025)
This research employs a qualitative research method with a literature study approach. The analysis uses literature analysis, literature review, and secondary data analysis. The object of the research uses 8 journal articles related to the evaluation of Islamic education published in the last 5 years (2020-2024) in national journals accessed through Google Scholar. The findings indicate that a balanced approach utilizing both traditional and digital evaluation methods, alongside quantitative and qualitative analyses, offers a holistic perspective on learning outcomes. The research underscores the importance of incorporating evaluation findings into curriculum development to ensure that Islamic education remains relevant and impactful. This study highlights the importance of providing teachers with intensive training to enhance teacher skills, creating valid and reliable instruments rooted in Islamic values, while leveraging technology to design adaptive assessments aligned with students’ needs. Evaluation findings should be integrated into the curriculum and learning improvements, fostering students’ ability to compete globally without losing their Islamic identity.